เปรียบเทียบกลยุทธ์การสื่อสารของรัฐบาลนางสาวยิ่งลักษณ์ ชินวัตรและรัฐบาลพลเอกประยุทธ์ จันทร์โอชา - เชือก โชติช่วย (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
This thesis analyzes and compare political communication strategies between governments of Miss Yingluck Shinawatra and General Prayuth Chan-o-cha. This research uses qualitative research method especially content analysis and the framework of political communication in democracy and authoritarianism. To do so, it analyzes contents from 2 television programs: "Yingluck’s Government talk with people" and "National Broadcast by General Prayuth Chan-o-cha" during the past 2 years. The research argues that the political leader who have different access to power, democratic leaders who comes from the election and the authoritarian leadership of the coup, uses different communication strategies. Word usage reflects the nature of the power of each political leader. Contents of communication, policy and response to the problems also demonstrate different communication strategies to preserve power and ensure potential to return to power afterward. While democratic leader uses the legitimization and delegitimization strategy, the authoritarian leadership uses the coercion strategies.